Baller-Gerold Syndrome. About a Clinical Case and Review of the Literature - Anolys Narciso Piña Rodríguez; Osiris Intento García; Sady Montes Amador (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Baller-Gerold syndrome is secondary to mutations in the RECQL4 gene (8q24.3). This gene belongs to the RecQhelicase family and is implicated in other diseases predisposing to cancer. Diagnosis is based on clinical criteria and due to the high number of differential diagnoses, finding a mutation in the gene can help to specify the diagnostic spectrum, genetic counseling and treatment. Around 30 cases have been described in the literature, although it is known that it has occurred in less than 200,000 people in the world, being considered a rare clinical condition. We present the case of a newborn, who at birth was found to have multiple musculoskeletal malformations: radial aplasia, aplastic thumbs, malformations of the rib cage, clinodactyly of all the fingers of the upper limbs, hypoplastic forearms, clinodactyly of the left lower limb. She was given parenteral feeding for several days, it was impossible to establish an adequate oral route due to the absence and/or incoordination of the sucking-swallowing reflexes as an expression of her malformations at the central nervous system level. The case is presented due to its low incidence and prevalence, which is why it is considered a rare disease.